Anharmonic kinetics of the cyclopentane reaction with hydroxyl radical. Issue 9 (3rd February 2020) - Wu, Junjun; Gao, Lu Gem; Ren, Wei; Truhlar, Donald G.
Abstract : Quadratic–quartic bend anharmonicity and torsional anharmonicities play important roles in the kinetics of a cyclic hydrocarbon. Abstract : Cyclopentane is one of the major constituents of transportation fuels, especially jet fuel and diesel, and also is a volatile organic compound with a significant presence in the atmosphere. Hydrogen abstraction from cyclopentane by hydroxyl radical plays a significant role in combustion and atmospheric chemistry. In this work we study the kinetics of this reaction at 200–2000 K using direct dynamics calculations in which the potential energy surface is obtained by quantum mechanical electronic structure calculations. The forward and reverse barrier heights and reaction energies obtained by the CCSD(T)-F12a/jun-cc-pVTZ coupled cluster calculations are used as a benchmark to select an accurate electronic structure method among 36 combinations of exchange-correlation functional and basis set. The selected M06-2X/MG3S method shows the best performance with a mean unsigned deviation from the benchmark of only 0.22 kcal mol −1 for reaction energies and barrier heights. A quadratic–quartic function is adopted to describe the ring bending potential of cyclopentane, and the quartic anharmonicity in the bending mode is treated by a one-dimensional Schrödinger equation using both Wentzel–Kramers–Brillouin (WKB) and Fourier Grid Hamiltonian (FGH) methods. The torsional anharmonicity in the transition state is treated in turn by the free rotor approximation, the one-dimensional hindered rotor approximation, and the multi-structural torsional anharmonicity method. Rate constants of the title reaction are computed by canonical variational transition state theory including tunneling by the multi-dimensional small-curvature tunneling approximation (CVT/SCT). The final rate constants include the quasiharmonic, quadratic–quartic, and torsional anharmonicity. Our calculations are in excellent agreement with all the experimental data available at both combustion and atmospheric temperatures with a deviation of less than 30%.